Seeing is believing: Tourism and foreign equity investments - Antoniou, Constantinos; Cuculiza, Carina; Kumar, Alok; Yang, Lizhengbo (Journal of Banking & Finance, 2025)
This study examines whether international tourism affects financial market investments. Using over two decades of data for more than 30 countries, we find that recreational travel between countries is associated with higher levels of foreign equity investments and reduced home bias. This evidence of tourism-induced foreign investment is consistent with the familiarity hypothesis and is unlikely to reflect superior information. We alleviate potential endogeneity concerns using several econometric techniques, including instrumental variables, quasi-natural experiments, and multiple placebo tests. Collectively, these results suggest that tourism has positive externalities in financial markets.